EXAMINING THE ECONOMIC IMPACT OF CORRUPTION: ARE DIFFERENCES BETWEEN THE CLEANEST AND MOST CORRUPT COUNTRIES BEFORE AND DURING COVID-19? - Lestari Agusalim; Muhammad Ilham Alfiansyah; Puguh Prasetyoputra; Riko Noviantoro (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
The relevance of this study stems from the need to understand the impact of corruption on economic growth across various groups of countries, particularly before and during the COVID-19 pandemic. This study aims to analyze whether there are differences in the impact of corruption on economic growth between countries with the lowest and highest levels of corruption, both before and during the pandemic. Using panel data regression analysis with a fixed-effects model from 2012 to 2020 and covering 159 countries, the study supports the "sand the wheels" theory, which suggests that corruption hinders economic growth. No significant differences were found in the effect of corruption on economic growth between countries with high and low corruption perception indices, both before and during the COVID-19 pandemic. Additionally, per capita spending and the quality of regulation positively impact economic growth. On the other hand, foreign direct investment (FDI) and trade openness have varying effects on economic growth across different groups of countries and periods. To mitigate the negative impact of corruption, stringent anti-corruption policies create an environment conducive to sustainable economic development.